ACTIVE LEARNING BASED ON BETTER TEACHING AND LEARNING (BTL) TO IMPROVE PROCESS SKILL AND STUDENTS STUDY RESULT (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
This research was conducted to describe the application of active learning based on Better Teaching and Learning (BTL) in improving process skill and students study result of grade VIII SMP N 21 Semarang. The methode is classroom Action Research. The research result reviewed that the increasethe process skill of students at cycle 1 and 2 are :80.95 and 94.29. While the studentsstudy result above passing grade at the cycles 1and 2 are: 74.0 and 77.0. This result research that applying active learning Based on Better Teaching and Learning could increase the process skill and study result of the students.